Continuity as Micropolicy of the Modern Companies - A. M. Vafin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
How to transfer power so that what has been created is not destroyed? This question is asked by politicians and business people from time immemorial. The problem of transferring power and management in general is relevant not only for monarchs, but also for business representatives. Provided that business is a family affair, the problem is doubled. The article analyzes various approaches to succession as a micro-policy process.